Central reader evaluation of MRI scans of the sacroiliac joints from the ASAS classification cohort: discrepancies with local readers and impact on the performance of the ASAS criteria. Issue 7 (5th May 2020) - Maksymowych, Walter P; Pedersen, Susanne Juhl; Weber, Ulrich; Baraliakos, Xenofon; Machado, Pedro M; Eshed, Iris; de Hooge, Manouk; Sieper, Joachim; Wichuk, Stephanie; Rudwaleit, Martin; van der Heijde, Désirée; Landewé, Robert B M; et al.
Abstract : Objectives: The Assessment of SpondyloArthritis international Society (ASAS) MRI working group conducted a multireader exercise on MRI scans from the ASAS classification cohort to assess the spectrum and evolution of lesions in the sacroiliac joint and impact of discrepancies with local readers on numbers of patients classified as axial spondyloarthritis (axSpA). Methods: Seven readers assessed baseline scans from 278 cases and 8 readers assessed baseline and follow-up scans from 107 cases. Agreement for detection of MRI lesions between central and local readers was assessed descriptively and by the kappa statistic. We calculated the number of patients classified as axSpA by the ASAS criteria after replacing local detection of active lesions by central readers and replacing local reader radiographic sacroiliitis by central reader structural lesions on MRI. Results: Structural lesions, especially erosions, were as frequent as active lesions (≈40%), the majority of patients having both types of lesions. The ASAS definitions for active MRI lesion typical of axSpA and erosion were comparatively discriminatory between axSpA and non-axSpA. Local reader overcall for active MRI lesions was about 30% but this had a minor impact on the number of patients (6.4%) classified as axSpA. Substitution of radiography with MRI structural lesions also had little impact on classification status (1.4%). Conclusion: Despite substantial discrepancy between central and local readers in interpretation of both types of MRI lesion, this had a minor impact on the numbers of patients classified as axSpA supporting the robustness of the ASAS criteria for differences in assessment of imaging.